Vitamin C in Cancer: A Metabolomics Perspective - Park, Seyeon; Ahn, Seunghyun; Shin, Yujeong; Yang, Yoonjung; Yeom, Chang H. (Frontiers in Physiology, 2018)
There is an ongoing interest in cellular antioxidants and oxidants as well as cellular mechanisms underlying their effects. Several reports suggest that vitamin C (L-ascorbic acid) functions as a pro-oxidant with selective toxicity against specific types of tumor cells. In addition, reduced glutathione plays an emerging role in reducing oxidative stress due to xenobiotic toxins such as metals and oxidants associated with diseases such as cancer, cardiovascular disease, and stroke. High-dose intravenous vitamin C and intravenous glutathione have been used as complementary, alternative, and adjuvant medicines. Here, we review the molecular mechanisms underlying the regulation of oxidation/reduction systems, focusing on the altered metabolomics profile in cancer cells following treatment with pharmacological vitamin C. This review focuses on the role of vitamin C in energy metabolism in terms of adenosine triphosphate, cysteine, and reduced glutathione levels, affecting cancer cell death.